Założenia metafizyczne w programie pozytywizmu logicznego - Firlej, Mateusz (Hybris, 2016)
In the present study I analyzed some aspects of the program of logical empiricism. I devoted particular attention to issues such as demarcation criterion, protocol sentence or logical syntax. These issues have been considered mainly through the prism of the work of Rudolf Carnap, while the contribution of other representatives of the Vienna Circle was rather kind of argumentative background. Mentioned philosophical trend had to stand in the closest possible touch with science. Therefore, fundamentally discredited metaphysical issues as meaningless. According to the author, such a radical distinction between sense and nonsense is unauthorized. Key neo-positivist postulates themselves are based on certain metaphysical assumptions.